Experimental Observation and Mitigation of Dielectric Screening in Hexagonal Boron Nitride Based Resistive Switching Devices. Issue 4 (3rd April 2018) - Wang, Bingru; Xiao, Na; Pan, Chengbin; Shi, Yuanyuan; Hui, Fei; Jing, Xu; Zhu, Kaichen; Guo, Biyu; Villena, Marco A.; Miranda, Enrique; Lanza, Mario
Abstract: Moisture and water penetration is one of the main phenomena altering the electrical characteristics and performance of resistive switching (RS) devices based on metal/insulator/metal nanojunctions. However, the effect of these phenomena in RS devices made of two dimensional (2D) materials has never been studied. In this paper it is shown that 2D materials based RS devices exposed to high relative humidity environments develop dielectric screening effects. The devices measured right after fabrication show a yield of 95% and bipolar RS characteristics, while after exposure to humid environments for two months the yield decreases to 65%. More than 30% of the devices show much lower currents than the fresh counterparts, and at high voltages they exhibit clear dielectric screening effects. This behavior is even more accentuated in RS devices that require the transfer of the 2D material, and we observe that a baking step at 120 °C for 5 min can mitigate this effect. Abstract : Dielectric screening is experimentally observed in hexagonal boron nitride based resistive switching devices. The penetration of moisture is the key factor producing a reduction of current and slow of the dielectric breakdown event. This behavior can be mitigated by adding a backing step during the fabrication process of the devices.